A typology of caregiving spouses of geriatric patients without dementia: caring, worried, desperate - Gehr, Thomas; Freiberger, Ellen; Sieber, Cornel; Engel, Sabine Alexandra (BMC Geriatrics, 2021)
Background: An increasing number of older people in Germany receive care at home from family members, particularly from spouses. Family care has been associated not only with subjective burden but also with negative effects on caregivers’ health. A heterogeneous group, caregivers are confronted with individual situational demands and use different available coping strategies. To date, little is known about the relationship between burden and coping by spousal caregivers, particularly in the context of geriatric patients without dementia. Objectives: The aim of this study is to explore the burden and coping strategies of caregiving spouses of geriatric patients without dementia and with a hospitalization within the last year. To help explore this population, a typology is presented that has been based on reported perceptions of home care burden and individual coping strategies. Furthermore, a case study is presented for each type of spousal caregiver. Methods: The study used a concurrent mixed method design with a sample of nine spousal caregivers (mean age: 78.9 years). Four women and five men were recruited in an acute hospital setting during the TIGER study. Quantitative data were collected using a self-questionnaire and qualitative data were gathered through nine problem-centered interviews with spousal caregivers. The latter were subsequently analyzed utilizing the structured content analysis method. The data were then summarized to nine individual cases. Finally, the results were clustered using the empirically grounded construction of types and typologies. Each type of spousal caregiver is presented by a case study. Results: Three types of caregiving spouses were identified: “The Caring Partner”, “The Worried Manager” and “The Desperate Overburdened”. These types differ primarily in the level of subjective burden and caregiving stress, the coping strategies, the motivation for caregiving, and expressed emotions. Conclusions: The development of this new typology of caregiving spouses could help health care professionals better understand caregiving arrangements and thus provide more targeted advice. Trial registration: The TIGER study was registered with clinicaltrials.gov: NCT03513159. Registered on April 17, 2018.
CRIS-Team Scopus Importer:2021-09-17
Keywords: Burden; Caregiver; Coping; Partner; Typology

“EduKation demenz® Nursing” in the acute hospital setting. Evaluation of a dementia training program: a pilot study - Gehr, Thomas; Sieber, Cornel; Freiberger, Ellen; Engel, Sabine Alexandra (Zeitschrift für Gerontologie und Geriatrie, 2021)
Background: An increasing number of people with dementia (PwD) are being hospitalized due to acute conditions. The surrounding conditions and procedures in acute hospitals are not oriented to the special needs of this vulnerable patient group. The behavior of PwD poses particular challenges and burdens for nursing staff. Objective: The aim of this pilot study was to evaluate the effectiveness of a 2-day dementia training program with a self-reflection component compared to a standard 1.5‑h training of nursing staff caring for PwD in acute hospitals. Methods: A nonrandomized pretest-posttest study with a control group was conducted in three German acute hospitals. Through a questionnaire, nursing staff caring for PwD were examined for potential changes in attitude, strain and confidence levels. The intervention group (n = 32) received a 2-day training program, “EduKation demenz® Nursing”, the control group (n = 36) participated in a short,1.5‑h dementia training. Results: Compared to the control group, the intervention group demonstrated statistically significant improvement in perceived strain (p = 0.007) and in confidence in caring for PwD (p < 0.001). There were positive but not significant changes in attitude (p = 0.176). Conclusion: “EduKation demenz® Nursing”, a 2-day training program with a self-reflection component, could provide more effective support for nursing staff in acute hospitals caring for PwD than a 1.5‑h training. Results indicate, however, that general conditions in acute hospitals should be changed to allow nursing staff to apply the knowledge gained.
CRIS-Team Scopus Importer:2021-01-22
Keywords: Dementia-sensitive care; Intervention; Qualification; Self-reflection; Strain

Functional status and quality of life of geriatric patients with wounds in acute hospitals A comparison between patients with acute and chronic wounds: a cross-sectional study - Lamotte, Sylvie; Rappl, Anja; Freiberger, Ellen; Sieber, Cornel; Gehr, Thomas (Zeitschrift für Gerontologie und Geriatrie, 2021)
Background Geriatric patients are more predisposed to the occurrence of wounds due to age and disease, affecting functional status and quality of life. This aspect has rarely been researched in this population. Objective The aim of this study was to investigate the influence of chronic (cW) and acute wounds (aW) on the objective functional status and wound-related subjective quality of life in hospitalized geriatric patients. Methods In this exploratory cross-sectional analysis, data from 41 patients with wounds were examined. Patients were participating and recruited in the TIGER study (n = 244). Depending on the type of wound, patients were assigned to the aW (n = 19) or cW (n = 22) group. The two groups were compared in terms of physical function, hand strength, activities of daily living, depression, cognition, nutrition, quality of life (Wound-QoL) and sociodemographic data. Results There was a significant difference between the aW and cW groups in terms of gender (p = 0.045) and living conditions (p = 0.047). The type of wound was associated with the Barthel index (p = 0.010) and the Wound-QoL (p = 0.022). Conclusion Compared to aW patients, cW patients were more limited in the physical and social dimensions and reported a lower quality of live. Living alone seems to play a relevant role. Among the patients of the TIGER study, men living alone were particularly more affected by cW. The care for these specific patients population should follow a holistic approach.
CRIS-Team WoS Importer:2021-10-15

Improvement of transitional care from hospital to home for older patients, the TIGER study: Protocol of a randomised controlled trial - Rimmele, Martina; Wirth, Jenny; Britting, Sabine; Gehr, Thomas; Hermann, Margit; Van Den Heuvel, Dirk; Kestler, Andreas; Koch, Thomas; Schöffski, Oliver; Volkert, Dorothee; Wingenfeld, Klaus; Wurm, Susanne; et al. (BMJ Open, 2021)
Introduction In Germany, an efficient and feasible transition from hospital to home for older patients, ensuring continuous care across healthcare settings, has not yet been applied and evaluated. Based on the transitional care model (TCM), this study aims to reduce preventable readmissions of patients ≥75 years of age with a transitional care intervention performed by geriatric-experienced care professionals. The study investigates whether the intervention ensures continuous care during transition and stabilises the care situation of patients at home. Methods and analyses Randomised controlled clinical trial, recruiting between 25 April 2018 and 31 December 2019 in one German hospital in the city of Regensburg. The intervention group is supported by care professionals in the transition process from hospital to home for up to 12 months. Based on TCM, the intervention includes an individual care plan according to a patient's symptoms, risks, needs and values. The plan is advanced in the domestic situation via personal visits and telephone contacts. All necessary care actions regarding, for example, mobility, residence adjustments, or nutrition, are initiated to be executed by ambulant care services, and are monitored, evaluated and adapted if necessary. In supervising the care plan, the care professionals do not administer active care services themselves but coordinate them. Patients and their caregivers are actively engaged in the care planning and execution. In contrast, the control group receives only usual discharge planning in the hospital and usual ambulatory care. The primary outcome is the all-cause readmission rate assessed using health insurance data within a follow-up of up to 12 months after hospital discharge. Secondary outcomes include care quality, mobility, nutritional and wound situation, and health-related quality of life. They are assessed at baseline, after 1 month, 3 months, 6 months, and at the end of study visit. Additionally, the economic efficiency of the intervention will be evaluated. Ethics and dissemination Ethics approval for the trial was obtained from the Ethics Committee of the Friedrich-Alexander-Universität Erlangen-Nürnberg. Results will be published in peer-reviewed, open-access scientific journals and disseminated at national and international research conferences and through public presentations in the geriatric and healthcare community. Trial registration ClinicalTrials.gov identifier: NCT03513159.
CRIS-Team Scopus Importer:2021-02-26
Keywords: clinical trials; geriatric medicine; internal medicine; public health; quality in health care; risk management